Liquid–liquid interfacial self-assembled triangular Ag nanoplate-based high-density and ordered SERS-active arrays for the sensitive detection of dibutyl phthalate (DBP) in edible oils. Issue 15 (7th July 2021) - Xu, Shuling; Li, Hefu; Guo, Meng; Wang, Lei; Li, Xia; Xue, Qingwang
Abstract : DBP, one of the phthalic acid esters (PAEs), is known as an endocrine disruptor and is toxic to humans in abnormal concentrations. Abstract : DBP, one of the phthalic acid esters (PAEs), is known as an endocrine disruptor and is toxic to humans in abnormal concentrations. Here, a high-density and ordered SERS substrate based on the self-assembly of triangular Ag nanoplate (TAgNP) arrays is developed for DBP detection. Benefiting from the ordered arrangement and sharp corners of TAgNPS, the arrays can provide sufficient and uniform hotspots for reproducible and highly active SERS effects. Using Rhodamine 6G (R6G) as a reporter molecule, the SERS enhancement factor (EF) of the TAgNP arrays was found to be as high as 1.2 × 10 7 and the relative standard deviation was 6.56%. As a trial for practical applications, the TAgNP array substrates were used for the detection of dibutyl phthalate (DBP) in edible oils. In this assay, edible oil samples were added to hexane as an organic phase for the formation of the TAgNP arrays, which caused DBP to be loaded at hotspots. DBP in edible oils could be identified at concentrations as low as 10 −7 M. This SERS substrate based on the TAgNP arrays has great potential applications in the high sensitivity and reproducible detection of contaminants in food.